Intraperitoneal transfusion for severe, early-onset rhesus disease requiring treatment before 20 weeks of gestation: A consecutive case series. (January 2020) - Crawford, Natalie E.H.; Parasuraman, Rajeswari; Howe, David T.
Abstract: Objective: To describe the management and perinatal outcomes of pregnancies affected by severe, early onset Rhesus isoimmunization treated with fetal intraperitoneal transfusions (IPTs). Study design: A ten-year consecutive case series of fetuses undergoing IPTs before 20 weeks gestation at Wessex Fetal Medicine Unit, Southampton, UK. Women with fetuses at risk of early onset fetal anaemia (before 20 weeks gestation) were identified from their obstetric history and maternal antibody levels at the time of booking. They were referred to our tertiary referral center. The decision to initiate transfusion was aided by middle cerebral artery peak systolic velocity as an indicator of fetal anaemia. No fetus was hydropic at the first transfusion. IPTs were commenced from as early as 15 weeks gestation in fetuses with difficult vascular access and performed regularly using this method until the cord could be successfully entered for intravascular transfusions. The main outcome measures were procedure and non procedure-related perinatal losses. Results: 11 fetuses underwent 45 IPTs. 10/11 (91%) were delivered after 33 weeks gestation. There was one perinatal loss 1/11 (9%: 95% C.I 1.6–38%) from a cord accident during intravascular transfusion at 26 weeks gestation. There were no procedure related fetal losses or complications at the time of early IPTs. Conclusions: Previous studies report a perinatal loss rate with early intrauterine transfusion of 24% in gestations below 20 weeks using the intravascular route. This series suggests that intraperitoneal transfusion can be a safe and effective treatment for severe fetal anaemia at early gestations where vascular access is difficult.